A photoactivatable theranostic probe for simultaneous oxidative stress-triggered multi-color cellular imaging and photodynamic therapy. (August 2022) - Chen, Xiaohui; Zhang, Zicong; Luo, Wenshuai; Zhuang, Zeyan; Zhao, Zujin; Wang, Lei; Wang, Dong; Tang, Ben Zhong
Abstract: Simultaneous in situ monitoring critical organelles upon oxidative stress and implementing therapeutics utilizing oxidative stress are of vital importance and remain challenging task. Herein, we rationally design and facilely synthesized a photoactivatable fluorescent probe bearing 1, 4-dihydropyridine moiety with aggregation-induced emission (AIE) tendency, namely TPA-DHPy, which can rapidly transform into its pyridine counterpart TPA-Py via photo-oxidative dehydrogenation showing strong polarity sensitivity and largely red-shifted emission. TPA-DHPy- and TPA-Py-based type I/type II photosensitization is able to effectively generate reactive oxygen species to induce in situ oxidative stress under white light irradiation. TPA-DHPy can be taken up by cancer cells, and gradually light up lipid droplets (LDs) and endoplasmic reticulum (ER) during photoactivatable process, as well as in situ monitoring difference and alteration of their microenvironment upon oxidative stress by means of multi-color fluorescence imaging in lambda mode. Furthermore, the in situ generated TPA-Py is capable of further destroying the functions of LDs and ER with prolonging the irradiation time, and remarkably inhibiting tumor growth under white light irradiation by the way of photodynamic therapy. This study thus offers useful insights into designing a new generation of theranostic agents towards imaging-guided precise cancer therapy.